O PROCESSO DE TOMADA DE DECISÃO DO ENFERMEIRO NO EXERCICIO DAS FUNCOES ADMINISTRATIVAS - Marcon, Patricia Maria; Meier, Marineli Joaquim; Wolff, Lilian Daisy G. (Cogitare Enfermagem, 2005)
Nota prévia